1999
DOI: 10.1111/j.1601-0825.1999.tb00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of integrin expression in oral squamous cell carcinomas

Abstract: OBJECTIVE: This study examines the intensity of expression of β1, α2, α3, α5, α6 integrin subunits in oral squamous cell carcinoma (SCC) as opposed to normal oral epithelium, and the intensity of expression and distribution pattern of the above subunits in relation to tumour differentiation grade. MATERIALS AND METHODS: Cryostat sections of 25 cases of oral SCC and 15 cases of normal oral epithelium were studied by immunohistochemistry (APAAP method). RESULTS: The intensity of expression of β1, α2 (Pearson χ2P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…At day 21, expression was clearly detected in the basal layer of the stratified epithelium (Fig. 6K), which is consistent with the expression pattern in normal mucosa [20]. On the other hand, CD49f was detected at cell surfaces not associated with the basement membrane, including the luminal surfaces of pseudostratified ciliated epithelium, simple epithelium and stratified epithelium in iPS cellderived teratomas, suggesting that CD49f has other roles independent of laminins (Fig.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…At day 21, expression was clearly detected in the basal layer of the stratified epithelium (Fig. 6K), which is consistent with the expression pattern in normal mucosa [20]. On the other hand, CD49f was detected at cell surfaces not associated with the basement membrane, including the luminal surfaces of pseudostratified ciliated epithelium, simple epithelium and stratified epithelium in iPS cellderived teratomas, suggesting that CD49f has other roles independent of laminins (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…It is expressed on the surface of basal keratinocytes [20], and high expression of CD49f is thought to be a marker of epithelial stem cells in mouse keratinocyte populations [34]. Moreover, CD49f expression is reduced significantly in oral squamous cell carcinoma [20]. In this study, CD49f was intensely expressed at the cell membrane in all types of epithelium observed in day-7 teratomas ( Fig.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Integrin alpha 6 and laminin alpha 5 chain are basement membrane com- ponents [7,8], and integrin alpha 6 is a specific component of hemidesmosomes [11]. Our findings indicated that the basal epithelial cells might adhere with hemidesmosomal attachments and generate the basement membrane.…”
Section: Discussionmentioning
confidence: 70%